Supervisory roles and influencing factors in enhancing EFL writing instruction: An analytical study - Aloairdhi, Nafilah; Alhojailan, Ahmad (Research Journal in Advanced Humanities, 2024)
The study explores the role of supervisors in English as a Foreign Language writing teaching in Saudi Arabia, bridging a significant gap in previous literature. Despite the tremendous hurdles that come with teaching writing successfully, supervisors act as educational leaders who guide and support teachers in adopting effective writing instruction techniques. The purpose of this study is to investigate the roles of supervisors in promoting successful EFL writing teaching, as well as the factors that influence their involvement in this context. The study used a qualitative technique, conducting semi-structured interviews with eleven professional educators at various educational levels. The data demonstrate a variety of supervisory techniques, highlighting differences in approaches between male and female supervisors, with female supervisors frequently having more stringent expectations for lesson design and strategy implementation. Additionally, cultural factors and external constraints have a substantial impact on supervisory positions, underlining the need of supervisors fostering a collaborative environment, prioritizing professional growth, and addressing cultural settings in their supervisory practices. The study finishes with recommendations and suggestions for further research. The findings provide important insights into the dynamics of EFL writing instruction and the role of supervisors in improving teaching quality in Saudi Arabia.